Addressing Infertility with Uterine Transplant: An Ethical Analysis of Three Categories of Donors - Garbuzova, Elizaveta (2021)
The first live births via uterine transplant using deceased donors (UTx) occurred in Brazil in 2017 and in the United States in 2019. Prior to that, living donors were the source of uteruses for transplant, with the first successful birth in Sweden in 2014, and the first successful birth in the US in 2017. This achievement in reproductive technology gives women with absolute uterine factor infertility (AUFI) the option to become a biological parent. In the US, 120,000 women of childbearing age are affected by AUFI. Without UTx, their only option for having genetically related children is through gestational surrogacy. Since some religions and cultures prohibit the use of surrogates to achieve motherhood and surrogacy is illegal in many countries, some women would not otherwise have the chance to have biological children. For instance, China, Finland, Germany, Iceland, and other countries prohibit any form of commercial or altruistic surrogacy making adoption the only option for becoming a mother. However, in many cultures, biological ties are central to the understanding of the family. For example, in the Middle East, adoption is uncommon because biological connections are crucial. Therefore, the only option these women would choose to become a mother is UTx. The exclusive value of UTx to these women is being able to experience pregnancy. Thus, UTx gives unique benefits to these women that adoption or surrogacy would not. The procedure entails surgery on a living or deceased donor to acquire the uterus. Then, the recipient undergoes transplantation followed by a course of immunosuppressive medication. After in vitro fertilization (IVF), the embryo is implanted into the transplanted uterus. If the pregnancy progresses, the child is delivered by C-section and the uterus is removed either simultaneously or later. This paper argues that both deceased and living donors should be permitted, while increased-risk donors should not be eligible.